2019
DOI: 10.1002/open.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin: The Case for Greener Production Driven by Sustainability Megatrend

Abstract: Approaching the end of the second decade of the 21st century, almost the whole demand of vanillin is met by the synthetic product obtained either via a petrochemical process starting from phenol and glyoxylic acid or from energy intensive alkaline oxidative depolymerization of lignin. Only a minor fraction is comprised of natural vanillin obtained from ferulic acid fermentation, and even less of highly valued Vanilla planifolia extracts. Are there alternative green production methods? And, if yes, are they sui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Compared to the natural source, chemically synthesized vanillin it is considerably cheaper ($15/kg), however, is labeled as artificial vanillin which attracts negative consumer sentiments. Various substrates have been tried for the synthesis of synthetic vanillin, like lignin, guaiacol, 4-hydroxybenzaldeyde, 3-bromo-4-hydroxybenzaldeyde, 3-methoxy-4-hydroxybenzyl alcohol, cow dung and lignin-rich crop residual waste materials with varying success (Banerjee and Chattopadhyay 2019;Ciriminna et al 2019).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Compared to the natural source, chemically synthesized vanillin it is considerably cheaper ($15/kg), however, is labeled as artificial vanillin which attracts negative consumer sentiments. Various substrates have been tried for the synthesis of synthetic vanillin, like lignin, guaiacol, 4-hydroxybenzaldeyde, 3-bromo-4-hydroxybenzaldeyde, 3-methoxy-4-hydroxybenzyl alcohol, cow dung and lignin-rich crop residual waste materials with varying success (Banerjee and Chattopadhyay 2019;Ciriminna et al 2019).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…In order to generalize the concept of installing the angelica lactone‐derived methylbutenolide chromophore onto biobased aldehydes to produce synthetic dyes, we extended the reaction to vanillin, a cheap commodity chemical isolated from processed lignin . Under the same general conditions ( 4 , Mn 2 O 3 , dioxane, reflux 14 h), 18 was obtained as a bright yellow solid in 84 % yield.…”
Section: Methodsmentioning
confidence: 86%
“…Therefore, vanillin has a great impact on the overall aroma of cork extracts. This compound is very characteristic for providing a very intense and pleasant aroma with sweet and floral notes, which is currently used in many different industrial fields, such as in the production of fragrances, in food use as in baking [25], or in cosmetics [11]. In addition, as was seen in other studies [26,27], vanillin is a natural bioactive component present in corks, which showed an Foods 2020, 9, 133 7 of 13 important antioxidant activity.…”
Section: Aromatic Characterizationmentioning
confidence: 86%